Can Dietary Fatty Acids Affect the COVID-19 Infection Outcome in Vulnerable Populations? - J. C. Onishi (American Society for Microbiology, 2020)
ABSTRACT There is high mortality in coronavirus disease 2019 (COVID-19)-infected individuals with chronic inflammatory diseases, like obesity, diabetes, and hypertension. A cytokine storm in some patients after infection contributes to this mortality. In addition to lungs, the intestine is targeted during COVID-19 infection. The intestinal membrane serves as a barrier to prevent leakage of microorganisms and their products into the bloodstream; however, dietary fats can affect the gut microbiome and may increase intestinal permeability. In obese or diabetic individuals, there is an increase in the abundance of either Gram-negative bacteria in the gut or their product, endotoxin, in systemic circulation. We speculate that when the COVID-19 infection localizes in the intestine and when the permeability properties of the intestinal membrane are compromised, an inflammatory response is generated when proinflammatory endotoxin, produced by resident Gram-negative bacteria, leaks into the systemic circulation. This review discusses conditions contributing to inflammation that are triggered by microbially derived factors from the gut.